ANALYSIS OF THE ARMONI CONCEPT IN CINEMA POSTERS: YEŞİLÇAM FILM POSTERS SAMPLE - ÖZEN, Yasemin (Atlas Journal, 2020)
A poster is a design produced in the field of graphic art that appears almost everywhere, gives a message to the audience, promotes an international or traditional culture. The poster design should aim to present the idea to the audience in the best way while promoting the target product. In order for the design to be good and captivate the viewer, the harmony in the poster, that is, the photograph or illustration created visually, the color, typography and balance should be analyzed very well and designed in harmony. The first meeting of cinema, which is a communication tool, with the audience is perhaps the poster. A good movie poster has a great influence on the success of a movie. The method of this study is to examine the concept of harmony, which includes color, balance, typography, photography and illustration criteria, on Yeşilçam movie posters. As a result, if the elements under the name of harmony used in poster design within the framework of the sample posters examined are not in harmony with each other and each element does not serve the product to be described in itself, a successful design will not emerge and the desired target audience cannot be reached. For this reason, the poster design should take into account the concept of harmony in order to achieve success.